RENEWAL OF THE CONSTITUTIVE NATIONAL LAW SYSTEM IN INDUSTRIAL DESIGN - Waspiah, Waspiah (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2022)
The regulation of industrial design in Indonesia is still experiencing several challenges, one of which is regarding the legal system. This paper aims to analyze the reform of the constitutive national legal system on industrial design in Indonesia. This paper confirms that the requirements for legal protection with a Constitutive system on industrial design by MSMEs required by law, if they are still used in the current era, where world developments are very fast, do not reflect the national legal system, so that what should be based on Pancasila as a legal ideal. An alternative step in bridging is to internalize Pancasila values into the Industrial Design Law as a spirit or soul which is expected to be able to provide justice for the Design Community (MSMEs).